2004
DOI: 10.1074/jbc.m401180200
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Proteolytic Processing of Extracellular Superoxide Dismutase (EC-SOD) is a Two-step Event

Abstract: Extracellular superoxide dismutase (EC-SOD) is a tetramer composed of either intact (Trpfor Gly enabled us to test these hypotheses. The mutation does not prevent proteolysis of the ECM-binding region but prevents a carboxypeptidase B-like enzyme from trimming residues beyond Gly 213 . The R213G mutation is located in the ECM-binding region, and individuals carrying this mutation have an increased concentration of EC-SOD in the circulatory system. In this study, we purified the R213G EC-SOD variant from hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…39,40 Our fluorescence cell sorting analysis showed that acute deletion of SOD3 leads to a striking pulmonary infiltration of various inflammatory cells. Among T cell subtypes, the increase in CD8 ϩ cells was greater than CD4 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Our fluorescence cell sorting analysis showed that acute deletion of SOD3 leads to a striking pulmonary infiltration of various inflammatory cells. Among T cell subtypes, the increase in CD8 ϩ cells was greater than CD4 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular pool of EC-SOD was enriched from cells transiently expressing wild-type EC-SOD. Cells were washed with Hanks' balanced salt solution; lysed by the addition of 25 mM Tris-HCl, 1 M NaCl, 0.5% (v/v) Triton X-100, and 5 mM EDTA (pH 7.4) containing 1 mM phenylmethylsulfonyl fluoride; and purified by immunoaffinity chromatography using a monoclonal antibody directed against human EC-SOD (16). Protein was eluted using 0.1 M glycine (pH 2.7), and fractions were immediately neutralized by the addition of 1 M TrisHCl (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…Here we report a case-control association study which examined the possible role of candidate polymorphisms in the genes encoding the antioxidant enzymes copper-zinc superoxide dismutase (SOD1), manganese superoxide dismutase (SOD2), extracellular superoxide dismutase (SOD3), and catalase (CAT). Specifically, we have targeted single nucleotide polymorphisms (SNPs) for their likely functional role: SOD1 +35 A/C which is located adjacent to a splice site, SOD2 Val16Ala which has been suggested to alter protein structure and function, 12 SOD3 213 (+760) C/G which has been shown to alter proteolytic processing, 13 and catalase 221 A/T which is located in the promoter region just proximal to the start site. 14 The SOD3 candidate polymorphism is of particular interest since the CRG substitution (+760) leads to an absence of cleaved SOD3 in the serum of carriers in a bimodal distribution.…”
mentioning
confidence: 99%